2003
DOI: 10.1046/j.1440-1681.2003.03857.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mushroom (Pleurotus ostreatus) ameliorates atherogenic lipid in hypercholesterolaemic rats

Abstract: 1. The effects of edible oyster mushroom Pleurotus ostreatus on plasma and liver lipid profiles and on the plasma total anti-oxidant status were estimated in hyper- and normocholesterolaemic Long Evans rats. 2. The feeding of 5% powder of the fruiting bodies of P. ostreatus mushrooms to hypercholesterolaemic rats reduced their plasma total cholesterol by approximately 28%, low-density lipoprotein-cholesterol by approximately 55%, triglyceride by approximately 34%, non-esterified fatty acid by approximately 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 33 publications
9
64
0
5
Order By: Relevance
“…The observation of reduced levels of total cholesterol, LDL-cholesterol and triglycerides in rats fed diets containing mushrooms is in agreement with results from other studies [21,22] that revealed that some edible mushrooms and their waterextract fraction have the capacity to lower the serum triglyceride concentration in spontaneously hypertensive rats and hyperlipidaemic rats. The results of this study also suggest that an increase in dietary cholesterol by even fairly low levels may be a pre-disposing factor for coronary heart problems.…”
Section: Discussionsupporting
confidence: 92%
“…The observation of reduced levels of total cholesterol, LDL-cholesterol and triglycerides in rats fed diets containing mushrooms is in agreement with results from other studies [21,22] that revealed that some edible mushrooms and their waterextract fraction have the capacity to lower the serum triglyceride concentration in spontaneously hypertensive rats and hyperlipidaemic rats. The results of this study also suggest that an increase in dietary cholesterol by even fairly low levels may be a pre-disposing factor for coronary heart problems.…”
Section: Discussionsupporting
confidence: 92%
“…However, these were not significantly different between C, T1 and T2. Some researchers have reported that cholesterol in serum decreased by additional levels of oyster mushroom in the diet (Bobek et al, 1998;Cheung, 1998;Hossain et al, 2003). Bobek et al (1991) also reported that whole mushroom retarded the increase in cholesterol in serum.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding of mushroom powder increases the excretion of total lipids and cholesterol through fecal matter. Mevinolin (a statin: Present in fruiting bodies of P. ostreatus and P. citrinopileatus) exhibited antihypocholesterolemic activities [54,55]. P. pulmonarius exhibited potent.…”
Section: Antilipidemic Activitymentioning
confidence: 99%